REPRESENTASI WACANA POLITIK PADA PEMBERITAAN KASUS SENGKETA PULAU REMPANG DI MEDIA MASSA ONLINE - Triadi, Rai; Shantika Regina , Frilia; Saeful Rachman, Reza (UNIVERSITAS PGRI YOGYAKARTA, 2025)
Representation of forms of political discourse is often carried out by politicians on various occasions. This is done as an implementation of a form of planned communication action to create the effect of favoring the public towards a figure or a political view. One of the opportunities used to represent a form of political communication is the case of the Rempang Island dispute. In this case, it can be seen that many of the responses given by various politicians took the form of siding with the community and were reported in online mass media. In this regard, in this study the researcher attempts to describe the forms of political communication actions, both carried out by individuals and community groups who responded to dispute cases on Rempang Island. In this research, the theory used is Norman Fairclough's theory of critical discourse analysis. This theory is used to see ongoing political communication practices through the dimensions of text, discourse practice, and sociocultural practice that form the background of the text or to see the original reality that makes the discourse emerge. Meanwhile, the data source for this research is news in online mass media regarding the Rempang case for the period July-October 2023